PERANAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM MENGOPTIMALISASI PELAYANAN GERAKAN INDONESIA SADAR ADMINISTRASI KEPENDUDUKAN (GISA) DI KOTA BANDUNG PROVINSI JAWA BARAT - Fadhil, Muhammad; Ilham, Muhammad (Registratie, 2019)
ABSTRACT This research focuses on describing and analyzing the role of the Department of Population and Civil Registration in optimizing the services of GISA (Population Administration Conscious Indonesian Movement) in Bandung City, analyzing inhibiting and supporting factors and providing strategies in optimizing the Population Administration Indonesia Movement (GISA). The researcher used the role theory in the implementation by Narwoko and Bagong and the theory of service quality dimensions by Zeithhaml, Parasuraman & Berry and conducted a SWOT analysis and litmust test to determine the strategy. The researcher used Qualitative theory with a descriptive approach. In collecting data, researchers conducted interview observations and collected documents about GISA services carried out by the Bandung City Population and Civil Registration Service. The results showed that 1) The role of the Bandung Population and Civil Registration Service was very vital in population services for the people of Bandung City, along with the times, DISDUKCAPIL had to innovate its population services to be accepted and implemented well by the Bandung City Community; 2) Inhibiting factors for optimizing the GISA program are the lack of socialization of GISA services by DISDUKCAPIL in Bandung City; 3) The strategy that must be done by DISDUKCAPIL in Bandung in optimizing GISA services based on SWOT analysis and litmust tests conducted by researchers includes: a) Increasing local government commitment in optimizing the GISA program, b) Increasing the socialization of GISA service programs to the people of Bandung, and c) Determination of APBD and APBDP in Bandung City must be on time. Keywords: GISA, Role in Implementation, Service Optimization ABSTRAK Penelitian ini memfokuskan untuk mendeskripsikan dan menganalisa peranan Dinas Kependudukan dan Pencatatan Sipil dalam mengoptimalisasi pelayanan GISA (Gerakan Indonesia Sadar Administrasi Kependudukan) di Kota Bandung, menganalisa faktor penghambat dan pendukung serta memberikan strategi dalam mengoptimalisasikan Gerakan Indonesia Sadar Administrasi Kependudukan (GISA). Peneliti menggunakan teori Peranan dalam pelaksanaan oleh Narwoko dan Bagong dan teori dimensi kualitas pelayanan oleh Zeithhaml, Parasuraman & Berry serta melakukan analisis SWOT dan litmust test untuk menentukan strategi. Peneliti menggunakan teori Kualitatif dengan pendekatan deskriptif. Dalam mengumpulkan data, peneliti melakukan observasi wawancara dan mengumpulkan dokumen tentang pelayanan GISA yang dilakukan oleh Dinas Kependudukan dan Pencatatan Sipil Kota bandung. Hasil penelitian menunjukkan bahwa 1) Peranan Dinas Kependudukan dan Pencatatan Sipil Kota Bandung sangat vital dalam pelayanan kependudukan bagi masyarakat Kota Bandung, seiring dengan perkembangan zaman, DISDUKCAPIL harus menginovasi pelayanan kependudukannya agar diterima dan dilaksanakan dengan baik oleh Masyarakat Kota bandung; 2) Faktor Penghambat pengoptimalan program GISA ialah kurangnya sosialisasi pelayanan GISA oleh DISDUKCAPIL Kota Bandung; 3) Strategi yang harus dilakukan DISDUKCAPIL Kota Bandung dalam mengoptimalkan pelayanan GISA berdasarkan analisis SWOT dan litmust test yang dilakukan peneliti antara lain: a) Meningkatkan komitmen pemerintah daerah dalam pengoptimalan program GISA, b) Meningkatkan sosialisasi program pelayanan GISA kepada masyarakat Kota Bandung, c) Penetapan APBD dan APBDP Kota Bandung harus tepat waktu. Kata Kunci: GISA, Peranan Dalam Pelaksanaan, Optimalisasi Pelayanan